Mathematical Model of Ultrasound Attenuation With Skull Thickness for Transcranial-Focused Ultrasound - Guo, Jiande; Song, Xizi; Chen, Xinrui; Xu, Minpeng; Ming, Dong (Frontiers in Neuroscience, 2022)
Transcranial focused ultrasound (tFUS) is of potential for both neuromodulation and neuroimaging. Due to the influence of head tissue, especially the skull, its attenuation is the key issue for precise focusing. The objective of the present study is to construct a mathematical model of ultrasound attenuation with skull thickness. First, combining with real skull phantom experiment and simulation experiment, tFUS attenuation of different head tissues is investigated. What’s more, based on system identification method, a mathematical model of ultrasound attenuation is constructed with skull thickness. Finally, the performance of the mathematical model is tested and the potential applications are investigated. For different head tissues, including scalp, skull and brain tissue, the skull is the biggest influencing factor for ultrasound attenuation, the attenuation caused by it is 4.70 times and 7.06 times that caused by the brain and scalp respectively. Consistent with the result of both simulation and phantom experiment, the attenuation of mathematical model increases with the skull thickness increasing. And the average error of the mathematical model is 1.87% in phantom experiment. Besides, experiment results show that the mathematical model is suitable for different initial pressures and different skulls with correlation coefficient higher than 0.99. Both simulation and phantom experiment validates the effectiveness of the proposed mathematical model. With the proposed mathematical model, the tFUS attenuation can be accurately calculated, which is significance for further research and application of tFUS.